2023
DOI: 10.3934/math.20231000
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced fault detection models with real-life applications

Abstract: <abstract> <p>Nonconforming events are rare in high-quality processes, and the time between events (TBE) may follow a skewed distribution, such as the gamma distribution. This study proposes one- and two-sided triple homogeneously weighted moving average charts for monitoring TBE data modeled by the gamma distribution. These charts are labeled as the THWMA TBE charts. Monte Carlo simulations are performed to approximate the run length distribution of the one- and two-sided THWMA TBE charts. The TH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Their results revealed that the AIB THWMA chart outperforms the classical THWMA chart, and both charts (i.e., THWMA and AIB THWMA) perform better than the DHWMA and AIB DHWMA, respectively. The THWMA chart for the time between events (TBE) was proposed by Lone et al [72]. In their paper, Lone et al [72] reported that the THWMA TBE outperforms the DHWMA TBE, HWMA TBE, EWMA TBE, and DEWMA TBE charts over a range of shifts.…”
Section: Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results revealed that the AIB THWMA chart outperforms the classical THWMA chart, and both charts (i.e., THWMA and AIB THWMA) perform better than the DHWMA and AIB DHWMA, respectively. The THWMA chart for the time between events (TBE) was proposed by Lone et al [72]. In their paper, Lone et al [72] reported that the THWMA TBE outperforms the DHWMA TBE, HWMA TBE, EWMA TBE, and DEWMA TBE charts over a range of shifts.…”
Section: Locationmentioning
confidence: 99%
“…The THWMA chart for the time between events (TBE) was proposed by Lone et al [72]. In their paper, Lone et al [72] reported that the THWMA TBE outperforms the DHWMA TBE, HWMA TBE, EWMA TBE, and DEWMA TBE charts over a range of shifts.…”
Section: Locationmentioning
confidence: 99%